Digital Learning Tools and their Role in Certification Preparedness Among Marketing Students - Almodovar, Tamara Marie; Cajayon, Alleah Shane; Dagandan, Aien Gabriel; Flores, Nievy Grace; Gulapa, Kenneth; Hadji Jalil, Almairah (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the role of digital learning tools in the certification preparedness of BSBA Marketing students at Eulogio “Amang” Rodriguez Institute of Science and Technology (EARIST)–Manila Campus. It aimed to determine the extent of students’ utilization of digital learning tools, assess their perceived learning effectiveness and certification preparedness, examine the relationship between digital learning tool utilization and certification preparedness, and propose an intervention plan to strengthen the integration of digital tools in marketing education. The study was anchored on the Input-Process-Output framework, where online and internet-based resources, student responses, and identified problems served as inputs; questionnaire formulation, validation, data gathering, statistical treatment, and interpretation served as processes; and the proposed intervention plan served as the output. A descriptive survey research design and cross-sectional survey method were used. The respondents were 124 fourth-year BSBA Marketing students selected through purposive sampling. A validated survey questionnaire was used to gather data, and the responses were analyzed using percentage, weighted mean, Likert scale interpretation, ranking, and t-test. The findings showed that the utilization of digital learning tools was Evident, with a grand mean of 4.08. The highest-rated area was integration with academic or training programs, followed by assessment and feedback mechanisms, accessibility and ease of use, interactivity and engagement features, and quality and relevance of learning content. Learning effectiveness was also rated Evident, with a grand mean of 4.04, particularly in knowledge acquisition and retention, problem-solving and analytical skills, application of marketing concepts, collaboration and peer learning, and motivation and study habits. Certification preparedness was likewise Evident, with a grand mean of 4.11, with strongest results in readiness for professional and industry expectations and technical skills and digital literacy. The study further found a significant relationship between digital learning tool utilization and certification preparedness at the 0.05 level of significance. The proposed intervention plan was rated Highly Acceptable, with an overall weighted mean of 4.31. The study concluded that digital learning tools support students’ certification preparedness by improving skill development, knowledge retention, digital literacy, confidence, and industry-relevant competencies, although challenges such as poor internet connectivity, limited device access, technical issues, and reduced engagement may affect their effectiveness. The study recommended stronger integration of certification-focused digital activities, online review sessions, digital simulations, interactive teaching strategies, improved technological infrastructure, technical support, and further research on related variables. The study aligns with SDG 4 – Quality Education, SDG 8 – Decent Work and Economic Growth, and SDG 9 – Industry, Innovation and Infrastructure. Its sustainability impact is mainly educational, institutional, technological, and socio-economic because it supports improved learning systems, workforce readiness, digital competency, and institutional capacity for certification preparation.